Ab initio calculations of 13C NMR chemical shielding in some N4O2, N4S2 and N6 Schiff base ligands containing piperazine moiety - Rezaeivala, Majid; Daftari, Sam (European Journal of Chemistry, 2014)
The calculation of 13C isotropic shielding constants by means of GIAO and CSGT methods of eight Schiff base ligands containing piperazine moiety at the Hartree-Fock and B3LYP levels of theory are presented. Good linear correlations between the calculated chemical shielding at gas-phase and experimental shift values in CDCl3 solution were obtained. Density functional theory (DFT) calculations at the B3LYP/6-31G(2d,p) level of theory is used to optimize the geometry of ligands. Calculated nuclear magnetic resonance (NMR) chemical shifts 13C are reported for the some N4O2, N4S2 and N6 Schiff base ligands containing piperazine moiety. In order to establish a convenient and consistent protocol to be employed for confirming the experimental 13C NMR spectra of Schiff base ligands, different combinations of models and basis sets were considered. The most reliable results were obtained at B3LYP/6-311G++ (d,p) level and CSGT method which can be used to predict 13C NMR chemical shifts with a very high accuracy for latter compounds. These results show the agreement between theoretical and experimental 13C NMR chemical shielding of mentioned ligands.